Watfa, Ägypten. Ausgrabungen in Watfa im Fayum und Bearbeitung der Michigan-Papyri aus Karanis. Bericht über das Grabungsjahr 2018/2019 - Römer, Cornelia (e-Forschungsberichte des DAI, 2019)
The life of the people in the Graeco-Roman Fayoum was characterized by the manyfold cultures, which coixisted in the villages founded in the 3rd century BC. Very ‘Greek’ were the gymnasia, institutions that resembled modern private sporting clubs. Such a gymnasium was first detected in 2017, and since then excavated in the village of Philoteris in north-western Fayoum. The gymnasium offered a large meeting hall, dining and lecture halls, and a race track fo the stadium run. Beside the gymnasium the focus of the archaeological work has been on the water management of the village and the question, when the water wheel was introduced in Egypt, the earliest facility to irrigate large fields mechanically. The project on the Michigan Papyri in the Egyptian Museum in Cairo, which deals with Greek texts excavated by the University of Michigan in Karanis between 1925 and 1936 was continued; a volume with editions of 35 new texts is to appear this year; among them, there is an oracle question to the god Soxis.